Companion cropping with potato onion enhances the disease resistance of tomato against Verticillium dahliae - Fu, Xuepeng; Wu, Xia; Zhou, Xingang; Liu, Shouwei; Shen, Yanhui; Wu, Fengzhi (Frontiers in Plant Science, 2015)
Intercropping could alleviate soil-borne diseases, however, few studies focused on the immunity of the host plant induced by the interspecific interactions. To test whether or not intercropping could enhance the disease resistance of host plant, we investigated the effect of companion cropping with potato onion on tomato Verticillium wilt caused by Verticillium dahliae (V. dahliae). To investigate the mechanisms, the root exudates were collected from tomato and potato onion which were grown together or separately, and were used to examine the antifungal activities against V. dahliae in vitro, respectively. Furthermore, RNA-seq was used to examine the expression pattern of genes related to disease resistance in tomato companied with potato onion compared to that in tomato grown alone, under the condition of infection with V. dahliae. The results showed that companion cropping with potato onion could alleviate the incidence and severity of tomato Verticillium wilt. The further studies revealed that the root exudates from tomato companied with potato onion significantly inhibited the mycelia growth and spore germination of V. dahliae. However, there were no significant effects on these two measurements for the root exudates from potato onion grown alone or from potato onion grown with tomato. RNA-seq data analysis showed the disease defense genes associated with pathogenesis-related proteins, biosynthesis of lignin, hormone metabolism and signal transduction were expressed much higher in the tomato companied with potato onion than those in the tomato grown alone, which indicated that these defense genes play important roles in tomato against V. dahliae infection, and meant that the disease resistance of tomato against V. dahliae was enhanced in the companion copping with potato onion. We proposed that companion cropping with potato onion could enhance the disease resistance of tomato against V. dahliae by regulating the expression of genes related to disease resistance response. This may be a potential mechanism for the management of soil-borne plant diseases in the intercropping system.